Executive Function Training Improves Emotional Competence for Preschool Children: The Roles of Inhibition Control and Working Memory - Li, Quan; Liu, Peiwei; Yan, Ni; Feng, Tingyong (Frontiers in Psychology, 2020)
The study examined how executive function (EF) training could improve children’s emotional competence (EC). Children (N=55; Mage=50.64 months) were assigned to two groups, namely the EF training group and the no-training group. The present study attempted to use a 2 (group: EF training VS no-training) × 2 (test time: pretest VS posttest) between-and- within-subjects design to investigate the effect of EF training on improving 4-year-old children’s emotional competence. Results showed that children attending EF training had significantly higher scores on emotional competence than that of no-training group. The change of inhibition control and working memory could significantly predict their variation of emotional competence. These results suggestted that EF training could improve children’s emotional competence. And furthermore, both inhibition control and working memory are taken to support a importance role on enhancing aspects of children’s emotional competence.